En alternativ ph.d.-afhandlings udfordring af den praktiske teologi - Schleicher, Marianne; Aune, Vigdis; Iversen, Hans Raun (Dansk Teologisk Tidsskrift, 2016)
Tenna Mose Rhiger has written a PhD dissertation in which she has developed a new approach to the celebration of service in the Evangelical Lutheran Church in Denmark with the aim of furthering the intimate presence of pastors during service. The purpose of this extended review of Rhiger’s dissertation is first to share the enthusiasm of the assessment committee for the project as well as its perspectives for Practical Theology and the celebration of service in the Evangelical Lutheran Church in Denmark. Secondly, the authors behind the review wish to advance some critical reflections on the formal requirements for similar experimental research projects in the future since this dissertation – as the pioneer work that it is – is likely to set the standards for “product dissertations” in the future.